PENINGKATAN MOTORIK KASAR ANAK USIA 4–5 TAHUN MELALUI PERMAINAN LOMPAT TALI DI TK MIFTAHUL ULUM TEGALGIRANG BANGODUA - Siti Nurhalimah; Irfan Fauzi Rahmat; M. Arif Syarif; Siti Nurhalimamh (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study was conducted based on the gross motor skill conditions of children aged 4–5 years at TK Miftahul Ulum Tegalgirang Bangodua, which still required improvement. Gross motor skills are an essential aspect of early childhood development as they support movement abilities, balance, body coordination, and children’s readiness to participate in learning activities. Although various physical activities have been implemented to stimulate children’s motor development, the use of rope skipping game as a learning medium for children aged 4–5 years still needs further investigation. This study aimed to improve children’s gross motor skills through the implementation of rope skipping games. The research employed a Classroom Action Research design using the Stephen Kemmis and Robin McTaggart model, conducted in two cycles involving 10 children in Group A. Data were collected through observation and documentation and analyzed using descriptive quantitative techniques with percentage analysis. The observed indicators included jumping ability, body balance, and movement coordination. The success criterion was achieved when most children reached the “Very Well Developed” category. The results showed a significant improvement across the cycles. In the pre-cycle stage, 60% of children were in the “Not Yet Developed” category. In Cycle I, 20% of children reached the “Very Well Developed” category, increasing to 80% in Cycle II, while the “Not Yet Developed” category decreased to 0%. Children also showed increased confidence during learning activities. In conclusion, rope skipping game was proven effective in improving gross motor skills of children aged 4–5 years, as indicated by the increase in the “Very Well Developed” category from 0% to 80%.